Sex Sounds: Vectors of Difference in Electronic Music - Sofer, Danielle (Cambridge, Massachusetts MIT Press, 2022)
"Music and sexuality seem to have been linked together since someone first beat out a rhythm on a drum. Making Sex Sound explores the intersection in the mid-20th century onward"--
Introduction -- Part I: Electroacoustics of the Feminized Voice. Schaeffer and Henry's "Erotica" (1950-51) ; Annea Lockwood's Tiger Balm (1970) ; Luc Ferrari's Les Danses Organiques (1973) and Presque Rien avec Filles, For Dancer and Memorized Sound (1989) ; Robert Normandeau's Jeu De Langues (2009) ; Juliana Hodkinson's and Niels Ronsholdt's Fish and Fowl (2011-12) -- Part II. Electrosexual Disturbance. Donna Summer's "Love to Love You, Baby" (1975) ; Alice Shield's Apocalypse (1990-94) ; Annie Sprinkle's Sluts and Goddesses Video Workshop, Sound Score by Pauline Oliveros (1992) ; Barry Truax's Song of Songs (1992) ; TLC's "I'm Good at Being Bad" (1999) ; Janelle Monae's "It's Code" (2013) ; The Wobble Warp : Theesatisfaction's "Enchantruss" (2012), Janelle Monaes and Esperanza Spalding's "Dorothy Dandridge Eyes" (2013), and Stas thee Boss's "Before Anyone Else" (2017) - Conclusion.
Includes bibliographical references and index.
Keywords: Electronic music; Music history; Cultural history